Preparation, oil adsorption behavior, and mechanism of micro/nanofibrous polycaprolactone membrane prepared through solution blow spinning. (5th December 2019) - Zhang, Tingting; Yang, Ruiting; Zhang, Xiaohui; Yin, Xueqiong; Tian, Hua; Zhu, Li
Abstract : In this paper, biodegradable polycaprolactone (PCL) was used as the raw material to prepare micro/nanofibrous polycaprolactone membrane (PCLM) through solution blow spinning (SBS) technology. The effects of spinning conditions (distance, gas pressure, and spinning solution concentration) on PCLM structures were investigated. The obtained membranes were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy, water contact angle, and thermogravimetric analysis instrument. The oil adsorbency and reusability of PCLM were measured. The oil adsorption capacity of PCLM for motor oil, peanut oil, and diesel oil was 15.93, 14.81, and 12.86 g·g −1, respectively. After 10 times of reuse, the adsorption capacity for motor oil, peanut oil, and diesel oil could still remain at about 80% of the first cycle. The kinetic and thermodynamic studies showed that the adsorption conformed to the first‐order kinetic model and Freundlich model. Thermodynamic parameters for oil adsorption Δ G θ, Δ H θ, and Δ S θ indicated the oil adsorption of PCLM was a spontaneous and physisorption process.